Quality AssessmentOfRice Noodles With Fortification Of Catfish(PangasiusHyphopthalmus) Protein Concentrate - Miftahul Amalia Rizki; Dewita Dewita; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe purpose of this research is to determine the effect of the addition catfish protein concentrate to the quality of rice noodles, so it is known the correct addition of catfish protein concentrate in processing of rice noodles,and observing the quality seen from organoleptik, moisture, protein, fat and ash contents. The design used was Completely Randomized Design non factorial which consistsof 4 treatment levels: K0 (0% catfish protein concentrate), K1 (5% catfish protein concentrate), K2 (10% catfish protein concentrate), and K3 (15% catfish protein concentrate). The parameters tested the values organoleptic and chemical analysis. Research on the level of confidence in 95% showed that organoleptic the best is K0with the characteristics of a white and very interesting (8,12), characteristics oftecture chewy, sticky and soft (8,01), characteristics of a distinctive smell rice noodle wet (8,52) and while the value of the treatment the best of catfish of protein concentrates 5% with characteristics of rice noodles wet and little smell of fish (8,79). While at the value of the chemical treatment best is the addition catfish of protein concentrates 15% it covers the water content 52,32%, high protein 22,23%, the ash 2,41% and addition catfish of protein concentrates 5% of levels of fat 0,19%. Keywords: protein concentrate, catfish, rice noodles